2015
DOI: 10.3109/02713683.2015.1024869
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ciliary Body Anatomy between American Caucasians and Ethnic Chinese Using Ultrasound Biomicroscopy

Abstract: Compared with the Caucasians, the Chinese had a thinner ciliary body and a more anteriorly positioned lens, which may contribute to more anteriorly positioned ciliary processes in this population. These findings might help to explain the higher prevalence of angle closure in the Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 24 publications
4
31
3
Order By: Relevance
“…Our study showed that APAC eyes had thinner ciliary bodies and smaller anterior ciliary processes than in the fellow eyes.. He et al [ 9 ] demonstrated that Chinese persons have thinner ciliary bodies than American Caucasians and postulated that this may be associated with the higher prevalence of angle closure in the Chinese population. In addition, a quantitative study of the ciliary body in eyes with malignant glaucoma showed thinner ciliary body in eyes with malignant glaucoma and in their fellow eyes, which might indicate a predisposing factor for malignant glaucoma [ 14 ].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our study showed that APAC eyes had thinner ciliary bodies and smaller anterior ciliary processes than in the fellow eyes.. He et al [ 9 ] demonstrated that Chinese persons have thinner ciliary bodies than American Caucasians and postulated that this may be associated with the higher prevalence of angle closure in the Chinese population. In addition, a quantitative study of the ciliary body in eyes with malignant glaucoma showed thinner ciliary body in eyes with malignant glaucoma and in their fellow eyes, which might indicate a predisposing factor for malignant glaucoma [ 14 ].…”
Section: Discussionsupporting
confidence: 51%
“…APAC was defined based on previous reported criteria: (1) the presence of at least two of the following symptoms: ocular pain, periocular pain or headache; (2) nausea and/or vomiting; (3) a previous history of intermittent blurred vision or halos around lights; (4) raised IOP of at least 25 mmHg; (5) and the presence of at least three of the following signs [ 7 ]: conjunctival injection, corneal epithelial oedema, mid-dilated unreactive pupil and/or a shallow anterior chamber. A primary angle closure suspect (PACS) eye was defined as a pigmented trabecular meshwork in the eye not visible or iridotrabecular contact (ITC) of 180 degrees or more under non-compressive gonioscopy (Goldmann), with normal IOP (<21 mmHg) and without peripheral anterior synechiae or glaucomatous neuropathy [ 2 , 8 , 9 ]. The choroidal thickness of all APAC eyes and their fellow PACS eyes were measured using SS-OCT. All imaging examinations were performed in 24 h right after the reduction of IOP by medication treatment (anti-inflammatory drops and/or a systemic steroid and hypertonic drugs) in affected eyes in order to ensure the corneal transparency, but before any procedures of peripheral iridectomy, iridoplasty or trabeculectomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that the RLP can provide an idea as to the ciliary process location [30]. Our noncycloplegic RLP results indicated that the lens was 0.09 units more posterior in the KC group than in the control group.…”
Section: Discussionmentioning
confidence: 48%
“…The characteristic boomerang-shaped iris in nanophthalmic eyes is thought to be an indirect indicator of anteriorly positioned ciliary processes. This physical displacement of the peripheral iris is associated with angle-narrowing and could result in goniosynechiae [ 26 ]. Hypertrophy of the ciliary body resulting from postoperative inflammation [ 25 ], annular ciliochoroidal effusion, or ciliary body detachment [ 27 ], and the relatively small space in the anterior segment in nanophthalmic eyes could result in the anterior positioning of the ciliary processes.…”
Section: Discussionmentioning
confidence: 99%